Lateral expansion and carbon exchange of a boreal peatland in Finland resulting in 7000 years of positive radiative forcing. Issue 3 (16th March 2017) - Mathijssen, Paul J. H.; Kähkölä, Noora; Tuovinen, Juha‐Pekka; Lohila, Annalea; Minkkinen, Kari; Laurila, Tuomas; Väliranta, Minna
Abstract: Data on past peatland growth patterns, vegetation development, and carbon (C) dynamics during the various Holocene climate phases may help us to understand possible future climate‐peatland feedback mechanisms. In this study, we analyzed and radiocarbon dated several peat cores from Kalevansuo, a drained bog in southern Finland. We investigated peatland succession and C dynamics throughout the Holocene. These data were used to reconstruct the long‐term atmospheric radiative forcing, i.e., climate impact of the peatland since initiation. Kalevansuo peat records revealed a general development from fen to bog, typical for the southern boreal zone, but the timing of ombrotrophication varied in different parts of the peatland. Peat accumulation patterns and lateral expansion through paludification were influenced by fires and climate conditions. Long‐term C accumulation rates were overall lower than the average values found from literature. We suggest the low accumulation rates are due to repeated burning of the peat surface. Drainage for forestry resulted in a nearly complete replacement of typical bog mosses by forest species within 40 years after drainage. The radiative forcing reconstruction suggested positive values (warming) for the first 7000 years following initiation. The change from positive to negative forcing was triggered by an expansion of bog vegetation cover and later by drainage. The strong relationship between peatland area and peat type with radiative forcing suggests a possible feedback for future changing climate, as high‐latitude peatlands may experience prominent regime shifts, such as fen to bog transitions. Key Points: Macrofossils, carbon accumulation, and age data from several cores were used to reconstruct three‐dimensional development of a Finnish bog The site experienced a spatially asynchronous succession leading to heterogeneous carbon dynamics Low carbon uptake and expansion of fen area caused 7000 year period of positive radiative forcing